1985
DOI: 10.1073/pnas.82.6.1643
|View full text |Cite
|
Sign up to set email alerts
|

Structure at 2.9-A resolution of aspartate carbamoyltransferase complexed with the bisubstrate analogue N-(phosphonacetyl)-L-aspartate.

Abstract: In an x-ray diffraction study by the isomorphous replacement method, the structure of the complex of aspartate carbamoyltransferase (EC 2.1.3.2) bound to the bisubstrate analogue N-(phosphonacetyl)-L-aspartate has been solved to 2.9-A resolution (R = 0.24). The large quaternary structural changes previously deduced by molecular replacement methods have been confirmed: the two catalytic trimers (c3) move apart by 12 A and mutually reorient by 10°, and the regulatory dimers (r2) reorient each about its twofold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
110
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 35 publications
3
110
0
Order By: Relevance
“…The percentage of identity for these positions versus the overall identity percentage for each pair of sequences from N. K Grishin and M.A . Phillips (1982), Ke et al (1984), Krause et al (1985), Kim et al (1987), Gouaux and Lipscomb (1988), Kantrowitz and Lipscomb (1988), Ke and Lipscomb (1988). References for TIM: Banner et al (1975), Wierenga et al (1987, , .…”
mentioning
confidence: 99%
“…The percentage of identity for these positions versus the overall identity percentage for each pair of sequences from N. K Grishin and M.A . Phillips (1982), Ke et al (1984), Krause et al (1985), Kim et al (1987), Gouaux and Lipscomb (1988), Kantrowitz and Lipscomb (1988), Ke and Lipscomb (1988). References for TIM: Banner et al (1975), Wierenga et al (1987, , .…”
mentioning
confidence: 99%
“…Isolated C trimers are readily dissociated into folded, inactive monomers upon treatment with NaSCN, and subsequent reconstitution studies have shown that the regeneration of enzyme activity is coincident with formation of the C trimer (6). Crystallographic studies of liganded and unliganded ATCase (7,8) and hybridization experiments with C subunits (5) have led to the Abbreviations: ATCase, aspartate transcarbamoylase; C trimer, catalytic trimer; Cxxx, C trimer with identity of mutated residue in the polypeptide chain designated by X subscript; subscript L, Lys …”
mentioning
confidence: 99%
“…The crystal structure of L-aspartate carbamoyltransferase, an enzyme of the pyridine nucleotide synthesis, known to utilize L-alanosine as an analogous substrate (Gale et al, 1968;Anandaraj et al, 1980) has been published (Honzatko, Crawford, Monaco, Ladner, Ewards, Evans, Warren, Wiley, Ladner & Lipscomb, 1982), but the site for L-aspartate binding could not be determined unequivocally from these studies. More recently, the crystal structure of the bisubstrate analogue, N-(phosphonacetyl)-L-aspartate with this enzyme was reported (Krause, Volz & Lipscomb, 1985). The dihedral angle for the C(2)-C(3) bond in this structure is 110 °.…”
Section: * Aicar Is 5-amino-l-(5-o-phosphono-fl-d-ribofuranosyl)-lh-mentioning
confidence: 85%